Dehydroacetic acid and its derivatives useful synthons in organic synthesis - Penta, Santhosh (Elsevier, 2017)
Dehydroacetic Acid and Its Derivatives: Useful Synthons in Organic Synthesis outlines the use of DHA and its derivatives for the synthesis of pharmacologically active heterocyclic compounds. Beginning with an introduction to the chemistry and reactivity of Dehydroacetic Acid, the book goes on to outline the key ring transformation reactions of DHA. The synthesis of various derivatives is then discussed, before a wide range of metal complexes of DHA are explored in detail. The book then concludes with a review of DHA’s biological importance and its impressive range of pharmacological activities, including anti-cancer, anti-bacterial, anti-fungal and analgesic properties. For those researching the synthesis of bioactive heterocyclic compounds, this book is a valuable guide on the fundamental knowledge needed to facilitate and enhance the successful synthesis of lead molecules--Provided by publisher.